Model Pembelajaran Value Clarification Technique (VCT) dalam Meningkatkan Kesadaran Sejarah Peserta Didik - Riza Umami; Nurul Umamah; Sumardi Sumardi; Riza Afita Surya (Universitas Negeri Padang, 2022)
Historical awareness is a demand that needs to be achieved in history learning in the 4.0 era by implementing paradigma mereka belajar and the 2013 curriculum. The low historical awareness of the younger generation in the 4.0 era can be seen from the implementation of learning history in school. This is in line with the results of the questionnaire in three schools which showed the low awareness of the history of students, as follows; 59.42% for SMAN 4 Jember, 50.33% for SMAN 1 Tanggul and 58.66% for SMAN 2 Tanggul. This study aims to determine the effectiveness of the implementation of the Value Clarification Technique (VCT) model in increasing students' historical awareness. This type of research uses qualitative experimental research. The sample of this study was 98 students from class XI of SMAN 1 Tanggul, SMAN 2 Tanggul, and SMAN 4 Jember. Data collection techniques using a questionnaire. The results of this study indicate an increase in students' historical awareness which can be seen from the four historical awareness indicators, as follows; (1) 74.36%; (2) 86.40%; (3) 73.51% and (4) 72.39%. Based on this research, the researcher suggests educators to create a history learning environment that provides freedom to express themselves, respect each other, be responsible and utilize technology by paying attention to the historical awareness of students and being innovative in choosing the learning model to be implemented.